2015
DOI: 10.1017/s0305000915000744
|View full text |Cite
|
Sign up to set email alerts
|

The limits of metrical segmentation: intonation modulates infants' extraction of embedded trochees

Abstract: A B S T R A C TWe tested German nine month olds' reliance on pitch and metrical stress for segmentation. In a headturn preference paradigm, infants were familiarized with trisyllabic words (weak-strong-weak (WSW) stress pattern) in sentence contexts. The words were presented in one of three naturally occurring intonation conditions: one in which high pitch was aligned with the stressed syllable and two misalignment conditions (with high pitch preceding vs. following the stressed syllable). Infants were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(73 reference statements)
1
7
0
Order By: Relevance
“…It is thus conceivable that nouns provide a gateway to language acquisition, independent of other properties that make early nouns special (e.g., concreteness, referentiality). Moreover, the results presented above provide an explanation of another finding from a recent segmentation study [13], which showed that only high-pitched stressed syllables (but not low-pitched ones) are taken as word onsets by German infants. The high frequency of LH*L in the corpus, compared to other patterns used in [13] (LL*H, HL*L), might account for this finding.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It is thus conceivable that nouns provide a gateway to language acquisition, independent of other properties that make early nouns special (e.g., concreteness, referentiality). Moreover, the results presented above provide an explanation of another finding from a recent segmentation study [13], which showed that only high-pitched stressed syllables (but not low-pitched ones) are taken as word onsets by German infants. The high frequency of LH*L in the corpus, compared to other patterns used in [13] (LL*H, HL*L), might account for this finding.…”
Section: Discussionsupporting
confidence: 74%
“…The authors argue that nouns are prosodically more salient than verbs due to the accentuation pattern of the sentence [12]. Furthermore, [13] demonstrate that German nine-month-olds only treat stressed syllables as word onsets when they are high-pitched. Investigating the frequency distribution of accentual patterns in IDS might help to understand these findings better.…”
Section: Introductionmentioning
confidence: 98%
“…In our view, the null effects of prosodic prominence in our recall task can be explained by a lack of a saliency effect, in the sense that the target items were not perceived to be prosodically different from the rest of the words in the child-directed discourse. It is well known that child-directed speech is characterised by a slower speech rate, higher pitch range, and larger F0 excursions than adult-directed speech (e.g., Zahner, Schönhuber, & Braun, 2016). In our materials, the short narratives presented to children contained a very systematic use of L+H* pitch accentuation.…”
Section: Discussionmentioning
confidence: 91%
“…Prosodic accentuation on the target word is essential for segmentation by 6-month-olds and facilitates segmentation for 9-month-olds, although it may become less important when infants are 12 months of age [83]. Moreover, exact alignment of the accentuated pitch peak with the stressed syllable of the word appears to be critical [84]. General prosodic exaggeration across the speech stream, as observed in infant-directed speech (IDS), facilitates segmentation on the basis of transitional probabilities in 8-month-olds [85] and possibly even newborns [86].…”
Section: Introductionmentioning
confidence: 99%